Evaluation of Glucose-6-Phosphate Dehyrogenase Deficiency in Patients with Sickle Cell Anemia - Defne Ay Tuncel; Şule Çalışkan Kamış; Begül Yağcı Küpeli (Van Tıp Dergisi)
INTRODUCTION: Aim: The study was to assess Glucose-6-Phosphate Dehydrogenase (G6PD) enzyme deficiency in Sickle Cell Anemia patients. METHODS: Between August 1, 2022, and August 1, 2023, we analyzed Sickle Cell Anemia patients admitted to Pediatric Hematology Oncology Adana City Training and Research Hospital.G6PD enzyme results obtained from standard tests were determined in these patients from hospital records. RESULTS: Twenty-three sickle cell anemia patients were detected from the hospital records. 34.8% of these patients were male and 65.2% were female (n = 15). The age range was between 4 and 30, with an average of twelve years. Twenty patients (87%) under the age of eighteen and three patients (13%) over the age of eighteen were found. The G6PD standard range is 2.22-36.98 U/g Hb and the average value is 26.28 U/g Hb. G6PD was detected in two out of twenty-three patients with a rate of 8.7%. When patients with G6PD enzyme deficiency were compared to those without, there was a borderline negative correlation in the frequency of blood transfusions (p: 0.052, r: -0.410). DISCUSSION AND CONCLUSION: It should be screened for G6PD deficiency to prevent their condition from deteriorating during treatment in Sickle Cell Anemia patients. Patients with Sickle Cell Anemia may experience worsening hemolysis if they co-inherit both diseases. Therefore, when choosing medications for SCA patients who have a G6PD enzyme deficiency, care should be taken.